A Review of Aboriginal Infant Mortality Rates in Canada: Striking and Persistent Aboriginal/Non-Aboriginal Inequities - Smylie, Janet (Can J Public Health, 2010)
OBJECTIVE: The Joint Working Group on First Nations, Indian, Inuit, and Métis Infant Mortality of the Canadian Perinatal Surveillance System is a collaboration of national Aboriginal organizations and federal and provincial/territorial stakeholders. Our objective was to better understand what is currently known about Aboriginal infant mortality rates (IMR) in Canada. METHODS: As part of a larger international systematic review of Indigenous IMR calculation, we searched the published literature for original research regarding the calculation of First Nations, Inuit, and Métis infant mortality rates at the national and provincial/territorial level. SYNTHESIS: We identified major deficiencies in the coverage and quality of infant mortality data for Aboriginal populations in Canada. The review of provincial and territorial reporting of infant mortality for Aboriginal populations revealed substantial provincial and territorial variation in the way that birth and death data were collected. With respect to coverage, high-quality IMRs were available only for Status Indians and communities with a high proportion of Inuit residents. No rates were available for Métis or non-Status Indians. CONCLUSION: Striking and persistent disparities persist in the IMRs for Status Indians and in communities with a high proportion of Inuit residents, compared to the general Canadian population. There is an urgent need to work in partnership with First Nations, Indian, Inuit, and Métis stakeholder groups to improve the quality and coverage of Aboriginal IMR information and to acquire information that would help to better understand and address the underlying causes of disparities in infant mortality between the Aboriginal and non-Aboriginal population in Canada.